Domestication of the Papua endemic fish rainbow Kurumoi (Melanotaenia parva) through different feeding treatments for optimizing survival - Jasmani, Jasmani; Ramadani, Soraya; Lestari, Uun; Sri, Putri Meira Shyiang; Gulapapo, La Andi (Sangia Research Media and Publishing, 2025)
The Rainbow Kurumoi ornamental fish (Melanotaenia parva) is an endemic species of Indonesia, originating from Lake Kurumoi in Papua, and is currently experiencing high levels of exploitation. Immediate efforts to rescue and conserve the Rainbow Kurumoi fish are crucial to prevent its extinction. The development of Rainbow Kurumoi fish farming has significant potential, particularly in South Sorong, which serves as a center for the germplasm of the Rainbow Boesmani fish species. This study was conducted to evaluate the growth and survival of Rainbow Boesmani fish using different feeding programs and water quality management to enhance their production. The research was designed using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments tested were: A (pellets), B (Artemia), C (hair worms), and D (water fleas). Data were analyzed using a CRD, and if significant differences were found, a further Duncan’s test was performed. The results indicated that different feeding treatments had a significant effect on the absolute weight growth of Rainbow Kurumoi fish from the third to the sixth week. The feeding treatments also significantly influenced the increase in the absolute length of the fish from the first to the sixth week. The survival rate of the Kurumoi fish, when fed different diets, ranged from 70% to 83%, which is considered to be in the good category.